ISMIR : the newsletter of the International Sexual Minorities Information Resource. (Pittsburgh : ISMIR, 1995)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie: PO Box 81869, Pittsburgh PA 15217-0869
Engels
Periodiek